High rate of arterial complications in patients supported with extracorporeal life support for drug intoxication-induced refractory cardiogenic shock or cardiac arrest - Pozzi, Matteo; Koffel, Catherine; Djaref, Camelia; Grinberg, Daniel; Fellahi, Jean Luc; Hugon-Vallet, Elisabeth; Prieur, Cyril; Robin, Jacques; Obadia, Jean François (Journal of Thoracic Disease, 2017)
Background: Cardiac failure is still a leading cause of death in drug intoxication. Extracorporeal life support (ECLS) could be used as a rescue therapeutic option in patients developing refractory cardiogenic shock or cardiac arrest. The aim of this report is to present our results of ECLS in the setting of poisoning from cardiotoxic drugs. Methods: We included in this analysis consecutive patients who received an ECLS for refractory cardiogenic shock or in-hospital cardiac arrest due to drug intoxication. The primary endpoint of our study was survival to hospital discharge with good neurological recovery after ECLS support. Results: Between January 2010 and December 2015, we performed 12 ECLS. Mean age was 44.2±17.8 years and there was a predominance of females (66.7%). Drug intoxication was mainly due to beta-blockers and/or calcium channel inhibitors (83.3%) and 5 (41.7%) patients had multiple drugs overdose. Weaning rate and survival to hospital discharge with good neurological recovery were 75% (9 patients). Among patients weaned from ECLS, mean duration of support was 2.4±1.1 days. Three (25%) patients underwent ECLS implantation during cardiopulmonary resuscitation, 2 (66.6%) of them died while on mechanical circulatory support (MCS). Six (50%) patients developed lower limb ischemia. Each patient was managed with ECLS decannulation: 2 (16.7%) patients underwent a concomitant iliofemoral thrombectomy, 3 (25%) needed further fasciotomy and the remaining patient (8.3%) required an amputation. Conclusions: Refractory cardiogenic shock due to drug intoxication is still one of the best indications for ECLS owing to the satisfactory survival with good neurological outcome in such a critically ill population. Further data are however necessary in order to best understand the possible relation between drug intoxication and lower limb ischemia, which was quite superior to the reported rates.